Quantitative assessment of liver fibrosis and its stage in a rabbit model by using intravoxel incoherent motion diffusion-weighted imaging at a 3T magnetic resonance system - Chen, Fan; Yang, Jian-Qiong; Zhang, Xiao-Ming; Li, Rui; Chen, Tian-Wu; Chen, Yan-Li; Jiang, Yu; Wu, Lan (Translational Cancer Research; Vol 6, No 6 (December 28, 2017): Translational Cancer Research, 2017)
Background: To explore whether and how intravoxel incoherent motion (IVIM) diffusion-weighted imaging (DWI) at a 3T magnetic resonance scanner could monitor and stage liver fibrosis in a rabbit model. Methods: Fifty-six New Zealand white rabbits were given carbon tetrachloride to model liver fibrosis, and eight treated with normal saline served as control subjects. IVIM-DWI with eight b values of 0, 10, 20, 50, 100, 200, 800, 1,000 s/mm2 was performed on the 0, 6th, 8th, 10th and 12th weekends after modeling this disease. The stages of liver fibrosis (stages F0 to F4) were identified based on METAVIR classification system. The IVIM derived parameters (D*, pseudo-diffusion; D, pure molecular diffusion; and f, perfusion fraction) were quantitatively measured, and statistical analysis were performed for detecting and staging liver fibrosis. Results: Significant difference was found in D between normal and fibrotic liver (P